Kondisi Muara Porong Berdasarkan Indeks Klorofil-A Dan Total Suspended Solid (TSS) [ Estuary Porong Status Based On Klorofil-A Index And Total Sedimen Solid (TSS) ] - Sapto Andriyono (Jurnal Ilmiah Perikanan dan Kelautan)
Abstract The purpose of research is to measure of physic-chemist aquatic parameter on Porong Estuary. Survey method used to collection of data. The average of chlorophyll-a index are 0-9.5 µg/l (3-68 µg/l rise tide and 1-30 µg/l low tide). Hight concentration of TSS on rise tide is 232-700 mg/l and low tide is 124-424 mg/l. Plankton analysis find out 73.3% diatom, 20% dinoflagelatta and 6.67% cyaniphyceae.